Zagrebački prigradski promet - Bogović, Blaž (Promet - Traffic&Transportation, 2012)
The paper deals with current issues of Zagreb suburban traffic. A number of problems have been identified: obsolete infrastructure facilities, congested traffic routes, deficiency of transportation means and low level of transportation service. All this reflects upon energy and space utilization, deterioration of environmental balance, increased noise pollution, stress situations and inconveniences a person, i.e. a passenger experiences in traffic. The author discusses the need for radical changes in suburban traffic planning. These changes are seen in the introduction of railways becoming a major aspect of suburban transport, because the railways can provide transport of large numbers of passengers in short periods of time, while the identified negative aspects are being eliminated or reduced to the minimum. It is therefore necessary to conceive the new system of suburban transport. This could be materialized through the elaboration of the projects of complete suburban transport segment. This in the first place refers to the infrastructure contents as by-pass lines, Medvednica Tunnel, Samobor line, airport links, passenger terminals, stations with platforms at an elevation parallel with the floor of the cars and special train cars for mass transport of passengers with broad seiding doors for quick getting of and off the trains. This projects can be elaborated by and expert and specialist team organized a in a research institution to be assigned the task from the very beginning- i.e. from the